2012
DOI: 10.1590/s0004-27302012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Tendência da mortalidade por diabetes melito em capitais brasileiras, 1980-2007

Abstract: RESUMOObjetivo: Analisar o padrão de mortalidade por diabetes nas capitais brasileiras entre 1980 e 2007. Materiais e métodos: Foram calculadas taxas de mortalidade quadrienais e anuais, padronizadas por idade pela população mundial. Modelos de regressão linear foram estimados para análise da tendência nas capitais. Resultados: No primeiro quadriênio, a taxa mais elevada correspondeu a 42,89/100.000 em Aracaju e, no último, a 54,38/100.000 em São Luís. Foram observadas tendências estatisticamente significativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
1
12
0
4
Order By: Relevance
“…These diseases are known to involve lifelong expenditures not only with drugs, but also with exams and medical visits, with a consequent considerable onus for health services which tends to increase with population aging 1,2 . Among non-transmissible chronic diseases, particularly outstanding is diabetes mellitus due to its high prevalence 3 and to the fact that it is considered to be a risk factor for morbidity-mortality 4 because of the complications induced by systemic macro-and microvascular injuries 5 . In 2000 there were about 171 million diabetic people in the world and this number is estimated to increase to 366 million by 2030 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are known to involve lifelong expenditures not only with drugs, but also with exams and medical visits, with a consequent considerable onus for health services which tends to increase with population aging 1,2 . Among non-transmissible chronic diseases, particularly outstanding is diabetes mellitus due to its high prevalence 3 and to the fact that it is considered to be a risk factor for morbidity-mortality 4 because of the complications induced by systemic macro-and microvascular injuries 5 . In 2000 there were about 171 million diabetic people in the world and this number is estimated to increase to 366 million by 2030 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that this data is particularly important, since, previously, the data pointed to a greater trend of DM mortality in the states and capitals of the Northeastern region. [7][8] When the data were stratified by sex, a trend curve for the trend of mortality for women in the State of Ceará was denoted. It is shown that this data is consistent with those obtained at the national level and in the Northeast region.…”
Section: Resultsmentioning
confidence: 99%
“…6 In recent decades, the high mortality rates and the burden generated by the disease in the capitals and states of the Northeast region of Brazil have been verified. [7][8] The need to evaluate the parameters of illness and death of a population is highlighted because this analysis can subsidize the proposal of public policies and the assessment of the management and planning of promotion and prevention actions carried out by the health services. It is understood that, this approach can be given by the historical series study of mortality trend.…”
mentioning
confidence: 99%
“…The importance of the occurrence of DM2 lies in the morbidity and mortality associated with the disease. Recently published data indicates a signifi cant increase in deaths caused by DM2 in 25 Brazilian capitals cities (10) . In addition to the mortality, the consequences of DM2 on human health, such as problems related to vision, the heart and the circulatory system, sleep and back problems (11) , negatively aff ect the quality of life of suff erers.…”
Section: Discussionmentioning
confidence: 99%